Pengaruh Budaya Organisasi dan Kepemimpinan Kepala Sekolah terhadap Kinerja Guru - Minsarni Minsarni; Yasir Arafat; Mulyadi Mulyadi (ISEJ : Indonesian Science Education Journal, 2020)
The Influence of Organizational Culture and Leadership of Principal on Teachers’ Performance. This research aimed to determine and describe the influence of organizational culture and leadership of principal on teachers’ performance. This research was a quantitative method using a descriptive approach. The population was all teachers at SMA Negeri 1 Palembang, totaling 90 people and all of them were used as research samples. For collecting data was used instruments which was arranged in the form of a questionnaire and likers scale as answer choices from 66 statement items which were 20 questionnaires for organizational culture variable, 24 questionnaires for leadership of principal variable, and 22 questionnaires for teachers’ performance variable. The data obtained were analyzed using data description analysis, multiple linear regression, t test analysis, F test analysis, and coefficient of determination. Based on the result of data analysis, the research showed that: (1) organizational culture had a positive effect on teacher’s performance, (2) leadership of Principal had a positive effect on teachers’ performance, (3) Organizational culture and leadership of principal had a positive effect on teachers’ performance.